2019
DOI: 10.28945/4250
|View full text |Cite
|
Sign up to set email alerts
|

Turned Off from an Academic Career: Engineering and Computing Doctoral Students and the Reasons for Their Dissuasion

Abstract: Aim/Purpose: We sought to understand factors that dissuade engineering and computing doctoral students in the United States from pursuing a career in the professoriate. Background: Many PhD students start the doctoral process excited about the possibility of becoming a professor. After a few years of doctoral education, however, many become less interested in academic careers or even come to loathe the idea of a faculty position. Methodology: Participants in a larger study (N = 744) completed a comprehensive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 57 publications
1
16
0
Order By: Relevance
“…While the possible reasons individuals choose faculty careers are myriad, most explanations tend to recapitulate limited extant literature and/or recount anecdotal conversations with colleagues who chose the professoriate. However, empirical scholarship on the pursuit of faculty careers remains limited in the engineering education literature (Burt, 2019; McGee et al, 2019; McGee, Robinson, Bentley, & Houston, 2015). Developing an in‐depth understanding of the reasons why individuals choose this path requires both large‐scale surveys and zoomed‐in accounts that detail the how and why of their choices.…”
Section: Introductionmentioning
confidence: 99%
“…While the possible reasons individuals choose faculty careers are myriad, most explanations tend to recapitulate limited extant literature and/or recount anecdotal conversations with colleagues who chose the professoriate. However, empirical scholarship on the pursuit of faculty careers remains limited in the engineering education literature (Burt, 2019; McGee et al, 2019; McGee, Robinson, Bentley, & Houston, 2015). Developing an in‐depth understanding of the reasons why individuals choose this path requires both large‐scale surveys and zoomed‐in accounts that detail the how and why of their choices.…”
Section: Introductionmentioning
confidence: 99%
“…An area for further research and exploration could focus on the fact that all URM participants reported "unsupportive" or "hostile" environments during their graduate work and/or postdoctoral appointment, which resulted in uncertainty regarding their stamina and resiliency "to make it as a professor." This finding is supported in the works of Burt (2019) and McGee et al (2019) both of which highlight the importance of the PhD socialization process and how this experience can negatively affect an individual's desire to continue toward a career in the professoriate. Concern also was voiced regarding the competitive nature of the field, leading to an unhealthy work-life balance for the participants, as well as for their mentors and supervisors.…”
Section: Discussionmentioning
confidence: 71%
“…Half of all students entering graduate school in STEM fields consider a career in the professoriate desirable (McGee et al, 2019). This initial interest originating in the early experiences and family influences present in an individual's life (Burt, 2019), an attraction to academic work (Lindholm, 2004), the perception of research autonomy, independence and individual expression (Gibbs & Griffin, 2013;Lindholm, 2004), the allure of the university work environment (Lindholm, 2004), and as a platform to help others (Gibbs & Griffin, 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations